1994
DOI: 10.1002/jsfa.2740660209
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism and fate of [methyl‐14C] and [uronate‐6‐14C]pectin‐labelled dietary plant cell walls in the rat

Abstract: The metabolism of dietary plant cell walls (PCW) was followed in the rat using PCW isolated from spinach cell cultures which ~ere'~C-labelled in the galacturonic acid residues (using ~-[6-'~C]ghcuronic acid, 2 85% of the 14C was confined to the C-6 position of pectic galacturonic acid residues) or the methyl ester groups (using ~-[rnethyl-'~C]methionine, 90% of the 14C was confined to methyl ester groups and 10% of the 14C in methyl ether groups) of pectin. Eighteen hours after gavage, only 5-10% of the 14C wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…These results suggest that of the 693 g/d of GalA infused for 1 Pectin, only 9 g was undigested whereas the other 684 g were digested. Intestinal bacteria therefore degraded about 99% of the infused pectin, and this is in agreement with data from monogastrics (Cummings et al, 1979;Buchanan et al, 1994). Results were similar for experiment 2 with only 1% of infused GalA recovered in feces.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…These results suggest that of the 693 g/d of GalA infused for 1 Pectin, only 9 g was undigested whereas the other 684 g were digested. Intestinal bacteria therefore degraded about 99% of the infused pectin, and this is in agreement with data from monogastrics (Cummings et al, 1979;Buchanan et al, 1994). Results were similar for experiment 2 with only 1% of infused GalA recovered in feces.…”
supporting
confidence: 88%
“…Neutral detergent-soluble fibers (NDSF) are plant carbohydrates that are unavailable to mammalian digestive enzymes but are soluble in neutral detergent solution, thus making them available for metabolism by gut bacteria (Hall et al, 1999). Pectin is one class of NDSF and studies in monogastrics have shown that dietary pectin is completely degraded by resident intestinal bacteria (Cummings et al, 1979;Buchanan et al, 1994). Because pectin primarily provides energy, bacteria also require N for growth on pectin.…”
Section: Introductionmentioning
confidence: 99%
“…in the colon involves hydrolysis of both glycosidic bonds and ester bonds (Buchanan et al 1994a). Plant cell wall polysaccharides and lignin, which are However, it has not been established to what extent the resistant to the digestive enzymes of man, are major ester groups of plant cell walls are susceptible to hydrocomponents of dietary fibre, which by definition lysis in the upper gut.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolism and fate of pectin-labelled plant cell walls (PCW) was followed in male Wistar rats (Buchanan et al, 1994). The PCW were 14 C-labelled in the galacturonic acid residues (using D- [6-14 C] glucuronic acid, more than 85% of the 14 C was confined to the C6 position of pectic galacturonic acid residues) or in the methyl ester groups (using L-[methyl-14 C]methionine, 90% of the 14 C was confined to methyl ester groups and 10% of the 14 C in methyl ether groups).…”
Section: Ratsmentioning
confidence: 99%